HUBUNGAN KONSUMSI PROTEIN TERHADAP PERKEMBANGAN MOTORIK KASAR USIA 6 – 24 BULAN DI BETUN MALAKA - Guntur Christian Putra Ndolu; Ummy Maisarah Rasyidah; Elita Halimsetiono (CALYPTRA, 2022)
Abstract-- Gross motor development is a development that has a function to coordinate and control the central nervous system, peripheral nerves, and muscles. Slow gross motor development, autism, behaviour and language can be found in the golden age of children aged zero to five years. Disturbances in gross motor development can be caused by inadequate nutritional intake. One of the nutritional intakes that play a role in producing motor movements is protein. Insufficient protein consumption can lead to slow motor gross movement. This study aims to determine the relationship between protein consumption and gross motor development of children aged 6 - 24 months in Betun Malaka. This research is an analytical observational study with a cross-sectional approach, which was conducted in January – February 2022 with direct interviews FFQ semi quantitative and denver II questionnaires. The sample in this study has met the inclusion criteria and amounted to 75 respondents. The statistical test used spearman rank correlation analytic test, which serves to determine the value of the research p value, as a parameter to see the relationship between protein consumption and gross motor development of children aged 6 - 24 months in Betun Malaka. The results of this study show that if the p value = 0.002 (p<0,05), which means that there is a significant relationship between protein consumption and gross motor development of children aged 6 - 24 months in Betun Malaka, with r = 0,632. Conclusion is a relationship between protein consumption and gross motor development of children aged 6 - 24 months in Betun Malaka, with a strong level of correlation strength. Keywords: denver ii, ffq semi quantitative, motorik kasar, protein Abstrak-- Perkembangan motorik kasar merupakan perkembangan yang berfungsi untuk mengkoordinasi dan mengontrol sistem saraf pusat, saraf perifer otot. Perkembangan motorik kasar yang lambat, autism, perilaku dan berbahasa dapat dijumpai pada masa golden age anak usia nol hingga lima tahun. Terhambat perkembangan motorik kasar dapat disebabkan oleh asupan nutrisi yang tidak adekuat. Salah satu asupan nutrisi yang berperan dalam menghasilkan gerakan motorik adalah protein. Konsumsi protein yang kurang dapat menyebabkan gerakan motorik kasar terhambat. Penelitian ini bertujuan untuk mengetahui a d a n y a hubungan antara konsumsi protein dan perkembangan motorik kasar anak usia 6 – 24 bulan di Betun Malaka. Penelitian menggunakan metode observasional analitik dengan pendekatan cross-sectional, yang dilakukan pada bulan Januari – Februari 2022 dengan wawancara langsung FFQ semi quantitative dan denver II. Sampel penelitian ini telah memenuhi kriteria inklusi dan berjumlah 75 responden. Uji statistik yang digunakan yaitu uji analitik korelasi spearman rank, yang berfungsi untuk mengetahui nilai dari p value penelitian, sebagai parameter melihat hubungan konsumsi protein dan perkembangan motorik kasar anak usia 6 – 24 bulan di Betun Malaka. Hasil penelitian menunjukkan jika p value = 0,000 (p<0,05), yang berarti terdapat hubungan yang signifikan antara konsumsi protein dan perkembangan motorik kasar usia 6 – 24 bulan di Betun Malaka, dengan r=0,632. Terdapat hubungan antara konsumsi protein dan perkembangan motorik kasar anak usia 6 – 24 bulan di Betun Malaka, dengan tingkat kekuatan korelasi hubungan yang kuat. Kata kunci: denver ii, ffq semi quantitative, motorik kasar, protein